TILLERING PATTERN AND CAPACITY OF WHEAT CULTLIVARS INFLUENCED BY SOWING DATE, AND ITS RELATIONSHIP WITH GROWING DAYS DEGREES (GDDcͦ ) - & Jaddoa, Al – Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the Experimental field , College of agriculture , during the winter season of 2005 - 2006 . The objective was to investigate the pattern and capacity of five wheat cultivars as influenced by sowing date . Split- split plot design in the arrangement of RCBD with four replicates was used. Sowing dates (5/11, 25/11 and 15/12) occupied the main plots , while wheat cultivars (Al- Iraq , Tammouz-2 , Abu Ghraib -3 , Tahhadi and IPA-99) were in the sub–plots. All wheat cultivars within each sowing date followed similar pattern of tiller production, but they were different in the tiller duration within each sowing , in reaching the maximum tiller number and , hence , they differed in their final ear number . All cultivars followed increased linear equation from the beginning of tillering up to the maximum number of tillers.Plants of all cultivars in 5/11 and 25/11 sowing dates commenced tillering .after 22 days from sowing while in the third sowing date (15/12), they commenced tillering after 28 days .The maximum number of tillers was 3.9 per plant in the 25/11 sowing date after 72 days from sowing , while the maximum tiller number in the first sowing was 3.3 after 61 days from sowing .Total duration of tillering was 54 days for the second sowing date (25/11) while in the first (5/11) and third (15/12)sowings it was reduced to 39 and 36 days , respectively . Plants required an accumulated temperature between (300-350)C°to commence tillering , the value was 318.250 and 350.500 C°for the first and second dates , respectively , while for reaching the maximum tiller number plants of the second sowing date required (800-850) C°accumulated temperature. This value represents almost third of the total accumulated temperature in the whole growing season.There were no varietal differences in commencing tillering i.e plant of all cultivars in the first and second sowings commenced tillering after 22days from sowing ,while the plants of all cultivars in the third sowing , commenced tillering after( 28) days from sowing .IBA-99 cultivar sown in the first sowing gave the maximum tiller number (4.260 ) per plant compared with other cultivars.Al- Iraq cultivars sown in the second sowing gave the maximum tiller number (4.538) per plant with no significant differences with IPA -99.